Students with Disabilities in the Polish Educational System After the Political Changes (2007-2012) - Apanel, Danuta (Journal of the American Academy of Special Education Professionals, 2015)
In the period of the People’s Republic of Poland, there were almost no students with disabilities at universities. The legislative, organisational, social and educational conditions at universities and students’ dormitories made it impossible for people with disabilities to start higher education. In the period of serious socio-political, economic, and educational crisis which took place in Poland in the eighties, students and lecturers, as well as the whole society, fought for broadly defined freedom, and also the access to education in open-access institutions, without restrictions in the field of social background or state of health. The actions of a student organisation, the Independent Students’ Association (Niezalezne Zrzeszenie Studentów-NZS), were of great importance during the implementation of these changes. The organisation was founded in 1980 and it was an expression of a protest of student community against policies of the People’s Republic of Poland. NZS worked mainly in the field of politics and propaganda, organised demonstrations and strikes–it was opposed to the communist government, the lack of democracy, injustice and the lack of freedom of speech. The program of NZS aimed at changing communist political system, education and economic system. After the year 1989, the Independent Students’ Association begun the next phase of its activity and the profile of the organisation was changed. The aim was to fight for the interests of students and the development of cultural and entertaining activity, as well as social and educational conditions for students with serious problems resulting from their state of health.